World Bank Investor Confidence Survey : Evidence from the Quarterly Global Multinational Enterprises Pulse Survey for the Second Quarter of 2021 - Saurav, Abhishek; Kusek, Peter; Albertson, Mark (World Bank, Washington, DC, 2021)
As economic conditions begin to improve in the wake of the COVID-19 pandemic, foreign investors face new challenges that are impeding a complete recovery. Results from the latest round (Q2 2021) of World Bank Group’s quarterly pulse survey of Multinational Enterprise (MNE) affiliates suggests that despite output and demand reaching pre-pandemic levels on average, most firms are still facing adverse effects. The share of firms reporting at least one adverse impact of the pandemic continued to fall in Q2 to 73 percent compared to 93 percent in Q1 2021. Within the ten business dimensions measured, employment and investment saw the largest improvement from Q1, but new challenges are emerging. Worker productivity and liquidity have emerged, alongside input cost pressures and supply chain reliability, as areas of concern for a complete recovery. MNEs’ future investment plans have become slightly more optimistic, providing early signs of an improvement in the investment outlook. The share of surveyed MNEs expecting to increase investment over the next three years has reached a pandemic high (21 percent) – driven by changes or expected changes in regulations and policies for foreign investors as well as insourcing of production. At the same time, uncertainty remains the primary factor limiting the appetite of firms to invest. Results also show over half of surveyed firms were forced to lay off workers during the pandemic, but recruitment plans over the next three years indicate an expected net increase in workforce. MNEs are increasingly looking for highly educated workers with strong managerial, analytical, and problem-solving skills. While these survey results may not be generalizable to all developing countries, they are directionally indicative of MNEs’ experiences in developing countries.